Development of a Web-Based Youth Innovation Village System Using Laravel Framework: Author's Country: Indonesia (Buana Information Technology and Computer Sciences (BIT and CS), 2025)
Youth play a crucial role in social development and serve as agents of change contributing to national progress. Karang Taruna, as a youth organization, has a strategic role in enhancing social welfare, including in Mekarjati Village. Since its establishment on November 10, 2013, Karang Taruna Mekarjati has grown with 13 subunits in each neighborhood unit (RW), serving a community of 11,881 people. However, the organization's business processes, such as member registration, social activity management, leadership training, and the formation and monitoring of MSMEs or startups, are still conducted manually. This results in operational inefficiencies and increases the risk of administrative errors. This study aims to design and develop a web-based system called "Youth Innovation Village" to support the digitalization of Karang Taruna Mekarjati’s management. The system is built using the Laravel Framework, with process modeling based on Business Process Modeling Notation (BPMN), the PHP programming language, and the MySQL database. The software development approach used is Agile Scrum, allowing flexibility in adapting to the organization's needs throughout the system development life cycle. The results of this study indicate that the implementation of Youth Innovation Village significantly enhances the effectiveness and efficiency of Karang Taruna’s management. The system accelerates membership administration, optimizes social activity coordination, and provides direct benefits to the organization's members in Mekarjati Village. Through this digitalization, Karang Taruna can become more adaptive to technological advancements and expand its social impact more effectively.